A prospective study of patients with large congenital melanocytic nevi and the risk of melanoma - Ana Carolina Leite Viana; Eugênio Marcos Andrade Goulart; Bernardo Gontijo; Flávia Vasques Bittencourt (Sociedade Brasileira de Dermatologia, 2017)
Abstract: Background: Large congenital melanocytic nevus (LCMN) is considered a risk factor for melanoma, although the magnitude of this risk is controversial. Objective: To evaluate the risk of melanoma development in patients with LCMN seen at a dermatology referral center in Brazil during a twelve-year period. To the best of our knowledge, there are no published similar studies on large congenital melanocytic nevus in South America. Methods: Our prospective cohort included only patients with congenital nevi ≥20cm. The cumulative risk of developing melanoma and the standardized morbidity ratio were calculated for patients followed up prospectively for at least 1 month. Results: Sixty-three patients were enrolled in this study. One patient who developed melanoma prior to enrollment was excluded, and five were eliminated because of insufficient follow-up time. Mean follow-up for the remaining 57 patients was 5.5 years (median 5.2 years). Median age of entry into the study was 2.6 years. Most patients (75.4%) underwent only clinical observation. Melanomas occurred in 2 (3.5%) patients. Five-year cumulative risk for melanoma was 4.8% (95% CI: 1.9-11.5%). Standardized morbidity ratio was 1584 (95% CI: 266-5232, p<0.001). Study limitations: The small sample size reduces the accuracy of risk estimates. Conclusions: This study analyzed prospectively for the first time data from South America demonstrating that patients with LCMN have a higher risk of developing melanoma than the general population (p<0.001).